Comparison of stationary digital chest tomosynthesis to portable chest radiographs: A patient study - Courtney Wing; Elias Taylor Gunnell; Alex Billingsley; Umer Ahmed; Christina Inscoe; Muthu Sakthivel; Bryan Hoag; Ertan Pamuklar; Thad Benefield; Jianping Lu; Xiaohui Wang; Otto Zhou; et al. (PLoS ONE, 2026)
Background Portable chest radiographs are a vital tool for clinical evaluation. However, their value remains limited due to overlapping anatomical structures obscuring underlying pathologies. Chest tomosynthesis has been proposed as an alternative to CT for high resolution chest imaging; however, a portable tomosynthesis unit is currently lacking in the standard of care. Utilizing a carbon nanotube linear x-ray source array, our team has developed a stationary digital chest tomosynthesis (s-DCT) unit that enables tomosynthesis imaging without need for a moving x-ray source during image acquisition. Purpose The goal of our study was to evaluate the performance of portable s-DCT in patients with concurrent portable radiographs and recent cross-sectional chest CT imaging. Methods This study recruited twenty-seven outpatients with recent chest CT images. Twenty-two patients were imaged with a conventional radiograph unit and the s-DCT system. Three board-certified thoracic radiologists rated their confidence in evaluating ten criteria: nine anatomic criteria and one on indwelling hardware. Readers were asked if information was gained from chest tomosynthesis, and if a follow-up CT was recommended. Random effects modeling was performed to assess factors contributing to reader confidence. Results Twenty-two adult patients were successfully imaged. Overall, reader confidence with s-DCT was significantly higher than CXR (p = < 0.001). Higher confidence in tomosynthesis was associated with perception that tomosynthesis gave additional information over CXR (p = 0.05). There was no significant trend toward not recommending a CT (p = 0.47). Conclusion Stationary digital chest tomosynthesis is a superior alternative to portable chest x-ray for patients that cannot undergo CT examination.